Morphoanatomical Studies of Cassia occidentalis Linn. (Leguminosae) - Ahmad, Sameera Ahrar (Plantae Scientia, 2025)
Scientific characterization of medicinal plant species is fundamental for assessing their taxonomic identity and therapeutic potential. The present investigation documents the morphological and anatomical attributes of Cassia occidentalis L. (Kasondi), with emphasis on vegetative structures and vessel element features. Seed and leaf extracts were subjected to phytochemical screening, free amino acid profiling, and mineral analysis to evaluate their bioactive and nutritional constituents. The integrated data provide a pharmacognostic framework for the species and substantiate its recognized ethnomedicinal applications.